Invasive Alien Plants: Impacts on Development and Options for Management - Ellison, Carol A (CABI, 2017)
Invasive alien plants pose a major threat to agriculture, the natural environment and livelihoods worldwide and create challenges for development. This is especially the case for those who live and work in rural areas. This book, for the first time, brings together a wide range of invasive plant specialists from the Asia-Pacific region who shares their experience in addressing the problem and delivering solutions. Mikania micrantha is used as case study in the book as it exemplifies many of the issues that need to be addressed. This neotropical vine is a major weed across the tropical humid zones of the region, where it smothers agroforestry, home gardens, natural forests and plantation production systems. The book emphasises the social and economic implications of plant invasion, and discusses direct impacts on livelihoods and biodiversity. It explains how various approaches to management including traditional ecological knowledge and classical biological control can be keys to the delivery of sustainable solutions, focusing on experiences in India, Nepal, Papua New Guinea and China. The use of policy frameworks in biological control and other management measures are also described.